ESTUDO DA VIABILIDADE DE BACTÉRIAS PROBIÓTICAS EM BEBIDA LÁCTEA COM ADIÇÃO DE CISTEÍNA - FIORENTINI, ÂNGELA M.; BALLUS, CRISTIANO A.; BALBOM, EVERTON B.; OLIVEIRA, MARLON L. D.; KLAJN, VERA M. (Salão do Conhecimento, 2013)
Resumo